2019
DOI: 10.1016/j.stemcr.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Tracing and Cell Potential of Postnatal Single Progenitor Cells In Vivo

Abstract: SummaryUnderstanding the contribution of adult neural progenitor cells (NPCs) and their lineage potential is a great challenge in neuroscience. To reveal progenitor diversity and cell-lineage relationships of postnatal NPCs in the subventricular zone (SVZ), we performed in vivo lineage-tracing genetic analysis using the UbC-StarTrack. We determined the progeny of single SVZ-NPCs, the number of cells per clone, the dispersion of sibling cells, and the cell types within clones. Long-term analysis revealed that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Specific progenitor cells were targeted at E12 to track their adult cell progeny in the OB. StarTrack is a powerful tool to examine the fate and the clonal relationship between cells derived from specific progenitors in vivo, under both physiological and pathological conditions [15][16][17]21,25,[27][28][29][30][31][32][33]. This tool also allows progenitor cells to be tracked in vivo, avoiding genetic manipulation of the animals or viral injections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific progenitor cells were targeted at E12 to track their adult cell progeny in the OB. StarTrack is a powerful tool to examine the fate and the clonal relationship between cells derived from specific progenitors in vivo, under both physiological and pathological conditions [15][16][17]21,25,[27][28][29][30][31][32][33]. This tool also allows progenitor cells to be tracked in vivo, avoiding genetic manipulation of the animals or viral injections.…”
Section: Discussionmentioning
confidence: 99%
“…The past two decades have witnessed an accumulation of abundant evidence regarding such heterogeneity, not only in the OB, but also in the dorsal cortex [39], hippocampus [40], and cerebellum [30]. Moreover, recent data show the bipotent capacity of postnatal NSCs to generate OB interneurons and glia in the cortex and striatum [21]. NSCs generating OB cells follow highly patterned and complex behavior during embryogenesis [41,42], and at post-natal stages [13,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vertebrates, in vivo lineage tracing of single genetically marked neural progenitor cells (NPC) showed that some NPCs generate both neurons and glia, while other NPCs generate only specific glia types (astrocytes or oligodendrocytes) or only neurons 48 . There is no example that one type of glia derives from another type of glia.…”
Section: Discussionmentioning
confidence: 99%